Emergency department investigation of deep vein thrombosis. Issue 1 (1st January 2003) - Kilroy, D A; Ireland, S; Reid, P; Goodacre, S; Morris, F
Abstract : Objectives: To apply a previously validated clinical model for predicting pre-test probability of deep vein thrombosis (DVT) to patients attending an emergency department with symptoms suggestive of DVT and assess its reproducibility in the patient population. To measure the diagnostic value of the SimpliRED d -dimer assay in effectively excluding DVT. Method: Prospective study between March 1999 and October 2000 of adult patients attending with suspected DVT. Patients were assessed using Wells' clinical prediction tool and risk stratified. SimpliRED d -dimer estimations were then performed and compression ultrasonography arranged. The pre-test probabilities of DVT in the low, moderate, and high risk groups of Wells' original cohort were compared with the authors' figures and the sensitivity, specificity, and predictive values of the SimpliRED assay calculated for the patient population. Results: Application of Wells' criteria to patients in the department permitted stratification into high, moderate, and low risk groups (prevalence of DVT 58.3%, 8.9%, and 1.5% respectively). SimpliRED d -dimer assay sensitivity was 63.4% with specificity of 74.8%, with a likelihood ratio of 2.52 for a positive test and 0.49 for a negative test. Conclusions: Clinical risk stratification allowed patients to be categorised into high, moderate, and low risk groups, albeit with less discriminatory power than originally described by Wells. The low sensitivity of the SimpliRED d -dimer assay when used routinely in a busy emergency department raises substantial doubt over the use of this test to rule out DVT, even in low risk patients.